Economic activity of people with disabilities in the context of disability models - Maciąg, Rafał (Niepełnosprawność i praca: Wymiary, konteksty, perspektywy, 2024)
In Poland, there are quite low rates of economic activity and employment of disabled people compared to other European countries. Aim. The aim of the chapter is to indicate the reasons for the low economic activity rate in Poland in the context of theoretical models of disability. Problem. The prevailing attitudes in society are favorable towards social security, including the tendency to remain on a pension. The medical certification system is focused on the assessment of body functions, which is not conducive to referral to work, and the rehabilitation system is dispersed and unclear to patients. Method. The chapter includes a research review, literature analysis of the subject and official data. Results and conclusions. System of economic activity supported by the State Fund for Rehabilitation of Disabled People does not meet expectations. The individual (medical) model of disability persists, strengthened by family care for a person with disability. The International Classification of Functioning, Disability and Health (ICF), which is used in many countries and regions to assess work ability, is not implemented in Poland. To encourage changes decision-makers, doctors and employers, a broad discussion is needed on the use of procedures necessary to assess the potential of people with disabilities.